Efektivitas Pendekatan Komunikatif pada Mata Kuliah Menyimak dan Berbicara II - Timur Sri Astami; Rosita Ningrum; Felicia Budihardja (Lingua Cultura, 2013)
The previous research on Communicative Approach in language learning stated that there was a correlation between speaking and writing abilities, in which both of them belong to productive skill. By presenting effective results, the students’ speaking skills could be developed. Based on that previous result, this research was focused on between the receptive and productive knowledge, those were listening and speaking, especially on the respondents who were the beginners to know to what extent the level of their speaking competences. The research applied quasi experiment method without having control class to describe a learning process by applying communicative approach. Respondents were the second semester of Japanese department students, year 2012/2013. The research data was taken twice, in the pre-test and post-test time, as well as questionnaires to know the respondents’ results on the learning process. The results indicated that the average increase of class respondents’ achievement was 16.31 point, that was from 66.84 of pre-test score into 83.15 scores for the post-test. Questionnaires were used to know the students’ comments on the speaking class using communicative approach. It can be concluded that the results of speaking class using communicative approach is proven to be effective to develop beginner respondents’ ability to speak.